Experimental and modeling investigation of the acoustic behavior of sustainable kenaf/yucca composites. (1st December 2021) - Samaei, Seyed Ehsan; Berardi, Umberto; Soltani, Parham; Taban, Ebrahim
Highlights: Sound absorption coefficients of the samples made of Kenaf and Yucca fibers were studied. Kenaf fibers effectively dissipate energy of sound wave and enjoy high absorption. The effects of sample thickness and density the samples were investigated. A computational method for prediction of sound absorption coefficient was proposed. Predicted absorption coefficients have a good agreement with the measured data. Abstract: The increased awareness of environmental issues has motivated researchers and manufacturers towards the use of natural acoustic absorbers, which are environmentally friendly, sustainable, and relatively cheap. One approach in this direction is to explore the use of waste fibers for potential applications in sound absorption. This study investigates the acoustic behavior of kenaf and yucca waste fiber composites. To this end, yucca and kenaf waste fibers were collected. The separation and extraction of fibers from non-fibrous tissues and woody parts were carried out using the water retting technique. Afterward, yucca and kenaf fibers were blended with a mass ratio of 70:30, 50:50, and 30:70. Polyvinyl alcohol (PVA) was used as the binder to fabricate the composite samples. The acoustic performance of the composites was evaluated using the impedance tube technique. The frequency-dependent absorption behavior of the samples was also investigated using the Delany-Bazley (D-B), Garai-Pompoli (G-P), and Johnson-Champoux-Allard (JCA) models. An in-house developed Matlab code was used for the simulation of the 3D structure of the specimens, and flow resistivity was calculated by simulation of the airflow through the structure. Additionally, tortuosity, viscous, and thermal characteristic lengths were calculated by an inverse technique. It was found that samples of 100% kenaf fibers have the highest flow resistivity values. Flow resistivity decreased with decreasing the kenaf content in the composite samples. It was found that samples of 100% kenaf fibers exhibit promising performance at the low- and mid-frequency bands. A decrease in the amount of kenaf content led to the shift of absorption peak towards the high-frequency region. It was also found that the JCA model closely follows the trend of experimental data for the frequency range of 80–6300 Hz.